Penggemukan sapi menggunakan pakan tanpa hijauan (complete feed) di era pandemi covid-19 (Fattening of cow cattle using green-free feed (complete feed) in the covid-19 pandemic era) - Meles, Dewa Ketut; Mustofa, Imam; Wurlina, W; Hariadi, Masud (Buletin Pengabdian, 2021)
Problems in the COVID-19 pandemic era for cows cattle farmers were limited skills of farmers in processing of feed without forage in order to reduce production costs and anticipate prolonged droughts. The government's steps to overcome these problems are by providing business capital assistance, deferring loan payments, and assisting cows cattle farmers. The Regional Superior Product Development Program (RSPD) aims to determine the increase in body weight of various types of cattle using feed without forage and growth promoters in the COVID-19 pandemic era of SMEs of cows cattle fattening. Data was collected by interview/questionnaire methods and making feed without forage, growth promoter, and fermentor. The feed from RSPD was applied to five types of cows cattle (local cattle, ongole crossbreeds, madura cattle, limousin crossbreeds and Simmental crossbreeds). This activity was carried out from February until June 2021. The results showed that farmers skill in making feed without forage, growth promoters, and fermenters has been improved and also type of cows cattle with good weight gain has been determined. In conclusion, the production of feed without forage, growth promoters, and fermentor in the COVID-19 pandemic era could be done by the cattle farmers independently. Limousin and Simmental crossbreeds had good weight gain compared to local cattle, ongole crossbreeds and madura cattle.